Efektivitas Perawatan Paliatif Terhadap Kualitas Hidup Pasien Kanker Berbasis Rumah: Literature Review - Anita Ndruru; Sry Rumondang; Riswani Tanjung (Elisabeth Health Jurnal, 2023)
Introduction : Cancer is still a health problem with a high mortality rate. Cancer sufferers also experience symptoms that are very disturbing to comfort, causing a decrease in the quality of life of cancer patients. The palliative care program is a treatment using an approach method whose main goal is to improve the quality of life of cancer patients. This literature review is to provide an overview of the effectiveness of palliative care in improving the quality of life of cancer patients.Method : The search for literature reviews uses 3 databases that is Google Scholar, Science Direct, and Proquest. Articles used as literature sources were selected based on the established inclusion criteria, that is: 1) Journal publication in the period 2018-2023; 2) Population/sample aged ≥ 18 years; 3) The patient's diagnosis is cancer; 4) Home-based palliative care; 5) National & International accredited journals (ISSN, ISBN, DOI); 6) Full text articles.Result : There were 10 journals which stated that palliative care was effective in improving the quality of life of patients. The role of the family in palliative care has a positive impact on the patient's quality of life. Apart from family, assistance from health workers and cadres is needed to help maintain the patient's life, so that the patient can accept his current conditionConclusion : Home-based palliative care further enhances the patient's welfare, because the home is the most comfortable place and is the final resting place for them. With the support of palliative care provided by the family both physically, psychologically and basic needs the patient can reduce anxiety and increase a positive outlook on acceptance of his current body condition. Apart from the role of the family, health workers and health cadres also need to take part in palliative care.